2008
DOI: 10.1007/s12033-008-9034-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant MAP30 on Cell Proliferation and Apoptosis of Human Colorectal Carcinoma LoVo Cells

Abstract: MAP30, an attractive protein isolated from bitter melon, has been previously found to have the anti-tumor and anti-HIV activities. In this study, MAP30 was cloned and expressed and the effects of the recombinant protein on cell proliferation and apoptosis of human colorectal carcinoma LoVo cells were investigated. The results showed that the proliferation of LoVo cells were significantly suppressed by MAP30 in time- and dose-dependent manners at the concentration ranging from 0.67 to 4.67 muM. The apoptotic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…The magnitude of the IC 50 values of all the tested tumor cells were consistent with that have been reported in previous studies [18,19,40]. It was demonstrated that rMAP30 showed moderate cytotoxicity with IC 50 values than that of rMAP30 with HBD.…”
Section: Cytotoxicity Of Rmap30 and Rmap30-hbdsupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitude of the IC 50 values of all the tested tumor cells were consistent with that have been reported in previous studies [18,19,40]. It was demonstrated that rMAP30 showed moderate cytotoxicity with IC 50 values than that of rMAP30 with HBD.…”
Section: Cytotoxicity Of Rmap30 and Rmap30-hbdsupporting
confidence: 90%
“…Recently, interest in MAP30 has been rekindled by the reports about its potent anti-tumor activity against human cancer cell lines. It has been demonstrated that MAP30 exhibits antitumor effects against certain human tumor cell lines, such as brain glioblastoma, melanoma, prostate carcinoma, breast carcinoma, liver hepatoma, colorectal carcinoma, etc [16][17][18][19]. However, the bioactivity of MAP30 is relative weak compared with the cytotoxicity of type II RIPs, which may result from the low uptake efficiency by tumor cells, and it has become a formidable barrier in the clinical application [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lots of BME dietary supplement products are currently available and marketed in numerous health food stores worldwide. Nowadays, the antitumor activity of BME has even become one of the most attractive research areas, since the anticancer property of the extract against a wide variety of human cancers such as breast carcinoma, melanoma, myeloma tumor, skin tumor, prostatic carcinoma, colorectal carcinoma, epidermoid carcinoma, hepatoblastoma, brain glioblastoma, bladder cancer, cervical carcinoma, and ovarian carcinoma has been gradually discovered [115,168,169,[171][172][173]. BME is potent in its antitumor activity against different cancer cells probably due to the presence of some of its active components including triterpenoids like cucurbitacin B (cucB) and kuguacin J, flavonoids like rutin and naringin, and phenolic acids.…”
Section: Nutraceuticals and Traditional Medicinesmentioning
confidence: 99%
“…Previous studies indicated that MAP30 exhibits a variety of anti-infection, anti-diabetic, antiviral and antitumor bioactive effects (4)(5)(6)(7)(8)(9)(10). The antitumor ability of MAP30 has been the subject of previous studies (11)(12)(13)(14)(15). However, certain researchers have already noted the effects of MAP30 on the inhibition of U87 cells in screening for anticancer effects (3,7,16,17).…”
Section: Introductionmentioning
confidence: 99%